First in vivo evaluation of the mutagenic effect of Brazilian green propolis by comet assay and micronucleus test - Pereira, Alzira Danielly; de Andrade, Sergio Faloni; de Oliveira Swerts, Mario Sergio; Maistro, Edson Luis [UNESP] (Pergamon-Elsevier B.V. Ltd, 2008)
Propolis is a hive product containing chiefly beeswax and plant-derived substances such as resin and volatile compounds. Propolis has been used in various parts of the world as an antiseptic and wound healer since ancient times, and interest in the product has recently increased. Considering the lack of data concerning the in vivo mutagenicity of green propolis, the capacity of this natural product to cause damage to the DNA was evaluated, using the alkaline single-cell gel electrophoresis (SCGE) and micronucleus test, in the peripheral blood cells of mice. The doses tested by gavage were 1000, 1500 and 2000 mg/kg. Micronucleus and SCGE assays showed that green propolis caused an increase in the damage to DNA in the peripheral blood cells of mice. The polychromatic: normochromatic erythrocytes ratio was not statistically different from the negative control. Considering the doses and the results obtained in this study, the acute consumption of green propolis produced some mutagenic effects on the blood cells of mice. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: green propolis; micronucleus test; single cell gel electrophoresis; SCGE; comet assay; Baccharis dracunculifolia